Pengaruh Destinasi Wisata Menara Songket Terhadap Perkembangan UMKM Di Sekitar Kawasan Seribu Rumah Gadang Di Koto Baru Kabupaten Solok Selatan - Niko Taufiq Hidayat; Ariyun Anisah (Trending: Jurnal Manajemen dan Ekonomi, 2023)
In carrying out the whell of life, we cannot be separated from what is called UMKM. Where the role of UMKM is veri large for indonesia economic growth. So this study aims to determination the effect of the songket tower tourism destination on the development of UMKM around the seribu rumah gadang koto baru area sout solok regency. This type of research useh quantitatif descriptif research using primary data taken directly from the field obtained from questionnaires, interview, and observasi. The results of the study show that tourist destinations have a positive and significant effect on the development of UMKM as according to the t test that has been carried out. Which is the significance of the t test for the two dependent variables below 0.05. In addiction, table R2 show that the coefficient of determination or R square is 0,391 or equal to 39,1%, which means that tourist destination have a positive and significant effect on the development of UMKM.